Assessing Northwest Pacific Fishery Stocks Using Two New Methods: The Monte Carlo Catch-MSY (CMSY) and the Bayesian Schaefer Model (BSM) - Ren, Qing-qiang; Liu, Min (Frontiers in Marine Science, 2020)
The CMSY and Bayesian Schaefer model (BSM) methods were applied to assess data-limited fishery stocks in the Japan Sea and surrounding areas of the Northwest Pacific. Ten stocks including 4 fish species and 5 cephalopod species were assessed; the CMSY method was used in 3 stocks with catch data only, and the BSM method in 7 stocks with both catch time series and catch per unit effort (CPUE) data available. The two methods estimated the maximum intrinsic rate of population increase (r) and carrying capacity of each stock, which allowed the computation of maximum sustainable yield (MSY), and exploited biomass relative to the biomass at maximum sustainable yield (B/BMSY). All 10 stocks were overfished, if to a different extent, and one, the spear squid (Heterololigo bleekeri) has collapsed. The reference points estimated here may be used as indicator for fishery management in this ecoregion.